Estimating Endogenous Effects on Ordinal Outcomes - Chesher, Andrew; Rosen, Adam M.; Siddique, Zahra (The Review of Economics and Statistics, 2025)
Abstract We examine the use of instrumental variable (IV) methods to measure the effect of a ceteris paribus change in an endogenous variable on an ordered outcome. Specifically, we use these methods to investigate the effect of neighborhood characteristics on subjective well-being (SWB) among participants in the Moving to Opportunity (MTO) housing voucher experiment. We find that the estimated positive effect of a decrease in neighborhood poverty on SWB is sensitive to the specification of the first-stage auxiliary equation for endogenous neighborhood poverty. Our results highlight the influential role of control function restrictions in complete triangular models.